Optimization of road-building materials from industrial waste (red mud, blast furnace slag, lime production waste, and natural loams) - Yelaman Kanatovich Aibuldinov; Galiya Zhanzakovna Alzhanova; Zhanar Baktybaevna Iskakova; Gaziz Galymovich Abdiyussupov; Madi Toktasynuly Omirzak; Aizhan Doldashevna Gazizova; Khristina Maksudovna Vafaeva (Frontiers in Materials)
The increase in industrial waste is a significant threat to the environment and economy, as most of it is non-biodegradable. The utilization of waste materials in road construction is effective in terms of recycling, economy, and ecology. The objective of the research is to investigate the potential use of four different industrial wastes – red mud (RM), blast furnace slag (BFS), lime production waste (LPW), and natural loam (NL) – as base materials in road construction. The mechanical and chemical properties of these materials were investigated through X-ray diffraction, X-ray fluorescence, atomic absorption spectroscopy, scanning electron microscopy, energy dispersive spectroscopy, and axial compressive strength testing. The structural performance was also conducted for different compositions of the materials by varying ratios of these materials. The results indicate that the combination of 40% RM, 35% BFS, and 8% LPW exhibited the maximum compressive strength of 14.21 MPa after 365 days with lower linear expansion. The mineral composition analysis confirms the absence of heavy metal contaminants and hazardous compounds, which will be environmentally friendly. The findings suggest that a mixture of RM, BFS, LPW, and NL can be considered construction materials in the transportation sector.